PEMANFAATAN BIJI PEPAYA (CARICA PAPAYA L.) SEBAGAI BIODIESEL DENGAN PROSES TRANSESTERIFIKASI IN SITU - Almukmin Umar; Fitria Fitria (Jurnal Teknik Juara Aktif Global Optimis, 2023)
Papaya plants have considerable potential and have not been widely developed, especially in the seeds because there is a high enough oil and protein content. The objective of this study was to investigate in situ transesterification process which allows direct production of biodiesel from papaya seeds. Changing conditions of the process variables studied were the volume of the methanol (100, 200, 300 mL) and time of process (15,30,45, 60, and 90 minutes) with a specified variables weight and water content of seed, catalyst, stirring speed, temperature and observable effect of the yield of oil extracted to form FAME. Volume of methanol and reaction time significantly affect the yield FAME. The highest FAME yield obtained on the volume of 300 mL methanol and 90 minutes time reaction (77,68%).